2018
DOI: 10.3390/jcs2030056
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Fiber Reinforced Plastics by Ultrasonic Welding

Abstract: Ultrasonic fabrication of fiber reinforced plastics made from thermoplastic polymer films and carbon or glass fibers enables cycle times of a few seconds and requires investment costs of only some 10,000 €. Besides this, the raw materials can be stored at room temperature. A fiber content of 33 vol % and a tensile strength of approximately 1.2 GPa have been achieved by ultrasonic welding of nine layers of foils from polyamide, each 100 µm in thickness, and eight layers of carbon fibers, each 100 µm in thicknes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…To this end, a suitable production technique needs to be found that is able to join the ECS with the composite patch. Here, the method of ultrasonic welding is used, which was described in depth by Gomer et al [30,31] This method is advantageous as it has short cycle times and allows patch manufacturing from raw carbon fabric and polymer film. Compared to conventional base materials such as prepregs or epoxy resin, these materials are harmless to health and less demanding in terms of storage conditions [32,33] .…”
Section: State Of the Art Crack Monitoringmentioning
confidence: 99%
See 4 more Smart Citations
“…To this end, a suitable production technique needs to be found that is able to join the ECS with the composite patch. Here, the method of ultrasonic welding is used, which was described in depth by Gomer et al [30,31] This method is advantageous as it has short cycle times and allows patch manufacturing from raw carbon fabric and polymer film. Compared to conventional base materials such as prepregs or epoxy resin, these materials are harmless to health and less demanding in terms of storage conditions [32,33] .…”
Section: State Of the Art Crack Monitoringmentioning
confidence: 99%
“…For the ultrasonic fabrication of CFRP, the carbon fibres are rolled off from a roving or a fabric roll, and the thermoplastic resin is given as a polymer film from polyamide 6 (PA6). Fibres and matrix are welded into a laminate by an ultrasonic welding machine in a single process, which can be broken down into five steps for easier description [31] . For the preparation of the process, fibres and matrix foil are stacked in layers (for the sake of simplicity one layer in Figure 4a).…”
Section: Stiffener Patch Designmentioning
confidence: 99%
See 3 more Smart Citations